Metallothionein 1X is a tumor suppressor gene and inhibits oxidative stress and metastasis in renal cell carcinoma - Rui Rui; Cong Huang; Yucai Wu; Heng Guo; Yanqing Gong; Xuesong Li; Liqun Zhou; Shiming He (Discover Oncology)
Abstract Metallothioneins 1X (MT1X) is expressed at low levels in renal cell carcinoma (RCC) and correlates with tumor progression, stage, grade and prognosis, but the mechanism of MT1X’s role in renal cell carcinoma is not fully understood at present, and the aim of this study was to investigate the molecular mechanism of MT1X’s role in renal cell carcinoma. We used immunofluorescence and flow cytometry to detect intracellular reactive oxygen species (ROS) levels and immunoblotting to detect the expression levels of key proteins of the epithelial-mesenchymal transition (EMT) signaling pathway, transwell assay to assess the cell migration and invasion capacity. It was found that MT1X knockdown significantly upregulated H2O2-induced intracellular ROS, activated the EMT pathway, and ultimately promoted cell migration and invasion whereas Trolox inhibited cell migration and invasion by suppressing the elevated ROS induced by MT1X knockdown. Here, we reported that MT1X is low-expressed in RCC and that MT1X knockdown promotes cell migration and invasion through the upregulation of intracellular ROS levels, thereby activating the EMT pathway.